The Influence Of Return On Assets, Current Ratio And Earning Pershare On Stock Prices Of Manufacturing Companies In The Consumption Industry Sector In The Indonesia Stock Exchange 2012-2015 - Isna Asdiani Nasution; Angelin (International Journal of Science, Technology & Management, 2021)
The objective of the research was to test and analyze the effect of Return on Assets, current ratio and earnings per share on share price of manufacturing companies of consumer goods in the Indonesia Stock Exchange in the period of 2012-2015. The research is used a quantitative research approach. The type of research is causal relationship. The nature of descriptive explanatory research was. The research populations were listed in the Indonesia Stock Exchange in the period of 2012-2015 manufacturing companies at consumer goods consisting of 37 companies. The research samples were 24 companies. The finding as well as the conclusion of research and return on assets affected by the share of manufacturing companies of the industry sector in the Indonesia Stock Exchange in the period of 2012-2015. Current Ratio did not affect share price of Manufacturing Companies in the Consumer Industry sector on the Indonesia Stock Exchange in the period of 2012-2015. Earning per Share affected Price of Shares of manufacturing companies of consumer industry on the Indonesia Stock Exchange in the period of 2012-2015. Simultaneously, Return on Assets, Current Ratio and Earning per Share affected share price of manufacturing companies of consumer industry sectors in the Indonesia Stock Exchange in the period of 2012-2015 known from its signficant level less than 0.05.